Recent Innovations and Nano-Delivery of Actinium-225: A Narrative Review - Sipho Mdanda; Lindokuhle M. Ngema; Amanda Mdlophane; Mike M. Sathekge; Jan Rijn Zeevaart (MDPI AG, 2023)
The actinium-225 (225Ac) radioisotope exhibits highly attractive nuclear properties for application in radionuclide therapy. However, the 225Ac radionuclide presents multiple daughter nuclides in its decay chain, which can escape the targeted site, circulate in plasma, and cause toxicity in areas such as kidneys and renal tissues. Several ameliorative strategies have been devised to circumvent this issue, including nano-delivery. Alpha-emitting radionuclides and nanotechnology applications in nuclear medicine have culminated in major advancements that offer promising therapeutic possibilities for treating several cancers. Accordingly, the importance of nanomaterials in retaining the 225Ac daughters from recoiling into unintended organs has been established. This review expounds on the advancements of targeted radionuclide therapy (TRT) as an alternative anticancer treatment. It discusses the recent developments in the preclinical and clinical investigations on 225Ac as a prospective anticancer agent. Moreover, the rationale for using nanomaterials in improving the therapeutic efficacy of α-particles in targeted alpha therapy (TAT) with an emphasis on 225Ac is discussed. Quality control measures in the preparation of 225Ac-conjugates are also highlighted.